Thoracic computed tomographic interpretation for clinicians to aid in the diagnosis of dogs and cats with respiratory disease. (November 2019) - Masseau, Isabelle; Reinero, Carol R.
Highlights: Thoracic computed tomography (CT) is a critical imaging modality for diagnosis of respiratory disorders in dogs and cats. Clinicians need to understand basic CT principles to facilitate optimal acquisition and interpretation of studies. Systematic interpretation uses a pattern-based approach including description of distribution and anatomic localization. Parenchymal patterns include increased lung attenuation, decreased lung attenuation, nodular opacities or linear opacities. Abstract: In humans, high-resolution computed tomography (CT) is a key diagnostic modality for pulmonary disorders. Its success likely lies in excellent correlation of lung diseases with associated subgross anatomic changes, as assessed by histopathology, and because of a multidisciplinary approach between clinicians, radiologists and pathologists. Although thoracic CT studies have been performed in dogs and cats for nearly three decades, there is a lack of uniformity in both protocols for acquisition and in terminology used to describe lesions. Importantly, terms such as a bronchial, interstitial, and alveolar patterns are inappropriate descriptors for canine and feline thoracic CT imaging changes; instead, lung patterns should be classified as increased or decreased attenuation, nodular patterns, and linear patterns, with specific vocabulary to describe subtypes of lesions. In this manuscript, the authors provide an overview of basic CT principles, strategies to optimize and acquire high-quality diagnostic studies (inclusive of paired inspiratory and expiratory series, contrast and triphasic angiography) and provide a roadmap for systematic interpretation of thoracic CT images.